1997
DOI: 10.1046/j.1365-2613.1997.240354.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of spontaneous renal lesion of APA hamsters by streptozotocin‐induced diabetes

Abstract: Syrian hamsters of the APA strain (APA hamsters) develop spontaneous mesangial thickening in the renal glomeruli from an early age. They also develop focal and segmental glomerulosclerosis (FSG) at and after 6 months of age. In this study, histopathological, immunohistochemical and lectin histochemical examinations were conducted to clarify the modification of the spontaneous renal lesions of APA hamsters by streptozotocin(SZ)-induced diabetes. Histopathological analysis revealed that the expansion of the mesa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
7
1
Order By: Relevance
“…Most of the studies using the STZ model of diabetes reported an increased synthesis of both glomerular matrix proteins: collagen type IV and laminin [17, 34, 35, 36]. However, using the very sensitive computer-aided image analysis technique for quantification of matrix proteins as done in the present study, we were unable to demonstrate an increased laminin synthesis.…”
Section: Discussioncontrasting
confidence: 76%
“…Most of the studies using the STZ model of diabetes reported an increased synthesis of both glomerular matrix proteins: collagen type IV and laminin [17, 34, 35, 36]. However, using the very sensitive computer-aided image analysis technique for quantification of matrix proteins as done in the present study, we were unable to demonstrate an increased laminin synthesis.…”
Section: Discussioncontrasting
confidence: 76%
“…APA hamsters show hyperlipidemia as well as hyperglycaemia, and develop diabetic complications similar to human diabetic diseases, such as atherosclerosis [17][18][19][20] and nephropathy [21,22]. In this diabetic animal model, probucol treatment ameliorates glucose intolerance and increases the insulin-positive area as a percentage of the whole pancreas area without a cholesterol-lowering effect [23].…”
Section: Introductionmentioning
confidence: 99%
“…Syrian hamsters of the APA strain (APA hamsters) are known to enter a marked and continuous diabetic state after a single injection of SZ without severe toxic effects [13,23,47]. Studies have also demonstrated that APA hamsters show hyperlipidemia as well as hyperglycemia and develop diabetic complications similar to human diabetic diseases, such as atherosclerosis [14,[46][47][48] and nephropathy [13,16,23].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also demonstrated that APA hamsters show hyperlipidemia as well as hyperglycemia and develop diabetic complications similar to human diabetic diseases, such as atherosclerosis [14,[46][47][48] and nephropathy [13,16,23]. We recently showed that SZ-induced APA hamsters keep a diabetic condition for a long period, because resident β-cells in islets proliferate after SZ injection, but they degenerate and secretion of insulin is maintained at low levels [37].…”
Section: Introductionmentioning
confidence: 99%